Evaluating the safety of diverse extracorporeal membrane oxygenation technologies through the lens of intensive care unit nurses’ perspective - Hakami, Emad; Mushqi, Basmah; Alsultan, Abdulsalam; Alsomali, Ahlam; Lo, Gretchen M. (International Journal of Research in Medical Sciences, 2025)
Background: Extracorporeal membrane oxygenation (ECMO) is a complex life-support technology increasingly utilized in intensive care units (ICUs). As ECMO devices diversify, ICU nurses are required to manage multiple platforms, posing potential challenges to care delivery and safety. Methods: A cross-sectional, descriptive survey was conducted among ICU nurses at King Faisal Specialist Hospital and Research Center, Riyadh. A validated questionnaire by Kiekkas et al was used to assess perceptions of ECMO technology’s positive and negative effects on nursing care. Descriptive statistics were calculated, and inferential tests (t-tests and one-way ANOVA) examined associations between perceptions and demographic characteristics. Results: A total of 97 ICU nurses participated. Respondents rated ECMO technology highly in enhancing patient safety (M=4.10, SD=0.92), improving nursing effectiveness (M=4.04, SD=0.97), and supporting professional development (M=4.10, SD=0.81). Negative perceptions included increased hospitalization costs (M=3.65, SD=1.16), nursing stress (M=3.35, SD=1.19), and mechanical risks (M=3.16, SD=1.19). No statistically significant differences in perceptions were observed based on gender, ICU experience, or educational level. Conclusions: ICU nurses generally perceive ECMO technology as a positive contributor to care quality and nursing efficiency, though concerns persist regarding cost, stress, and safety. The uniformity of perceptions across demographic subgroups may reflect practical institutional training and standardized ECMO protocols. Findings highlight the importance of involving nurses in equipment evaluation, training design, and interdisciplinary collaboration to ensure patient safety and staff well-being.